Komunikasi Interpersonal Marketing Communication PT Indo Asia Unggul dalam Penerapan Pelayanan Prima: (Studi Deskriptif Kualitatif pada Rak Suca Surabaya) - Devi Aprilia Putri Anggraeni; Ratna Setyarahajoe; Muhammad Fadeli (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
In the highly competitive retail distribution industry, service excellence has become a crucial differentiating factor. However, PT Indo Asia Unggul faces challenges arising from a gap between customer expectations and actual service delivery, which affects consumer satisfaction. This study aims to describe and analyze the interpersonal communication practices employed by the Marketing Communication division in implementing service excellence at Rak Suca Surabaya. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that interpersonal communication functions as a strategic instrument, revealing a distinctive hierarchy in which empathy is prioritized over openness, particularly in crisis, to mitigate the risk of service failure. Moreover, personal interactions enhance the persuasive function of marketing and act as an amplifier of product reliability (hard skills), although they cannot fully compensate for fundamental deficiencies in product quality. This study concludes that a strategic balance between communication competence and product quality is essential for fostering customer loyalty. Therefore, the formalization of empathy-based soft skill training is recommended for the company.